954 Pushing and pulling assessment: how to deal with inter-operator variability. (24th April 2018) - De Vito, G; Riva, MA; Marinelli, M; Vitale, A; Sormani, M; Belingheri, M; Turato, M; Latocca, R
Abstract : Introduction: Snook and Ciriello has been the leading methods to assess pushing and pulling for roughly 30 years. ISO11228-2 integrated it providing useful add-ons. On duties, workers apply excessive amount of force, for reasons either related to organisational, technical or legal issues. Therefore, inter-operator variability still remains a main issue to be addressed. Methods: 378 pushing and pulling test sessions were organised. Forces were measured by means of a computerised dynamometer (200 Hz, 120 Kg scale). 3 health operators (OH) and 2 very trained technicians (T) moved 2 types of hospital beds carrying simulated loads of patients weighting 70, 90 and 110 Kg, on a maximum distance of 300 m. To assess the speed limit (1 m/second) compliance, a 20 m pushing test was repeated multiple times by each tester. The same 20 m test provided individual threshold to compute initial and sustained forces. Initial force was defined as value lying above the threshold, the hysteresis curve and only for coherent data. To compare the speed suggested by the methods with the real speed performed by operators, a 2 months analysis of the patient transportation recorded missions was carried out. Then the accumulated delay-times were estimated with reference to the mean travel time measured at the suggest speed. Results: Initial forces resulted 43% (32%–112%) and sustained forces 37% (23%–101%) higher and statistically significant for OH compared to T. Increased speed saves only 25% (12%–56%) of the travel time, due to elevators waiting, doors opening etc. Conclusion: Rapidly grooving hospitals often show tortuous paths, where patient transportation on bed is allowed. ISO11228-2 assessment method contribute to solve complex measures, particularly when dealing very long distance pushing and pulling tasks. Initial forces might be calculated by measuring the threshold of the initial force of each operator on a 20 m test. Mean delay time shows risk excess often leading to increased speed behaviours.